Barley derived spent grains: conversion to bioethanol - Wilkinson, Stuart (2016)
Brewers spent grains (BSG) are an abundant co-product from the beer brewing industry. The current predominant use for BSG is as cattle feed. However, this is a low value use. As such, higher value uses for BSG are being sought. One such option is the production of bioethanol from the polysaccharides (cellulose and hemicellulose in the lignocellulosic matrix) found in BSG, and this thesis aimed to develop this process. This was achieved through investigating and attempting to optimise a range of different pre-treatments in order to enhance the subsequent cellulolytic enzyme saccharification yields to produce a high glucose concentration feedstock which could then be fermented to produce bioethanol. For the pre-treatment step of the process, a wide range of protocols were investigated and optimised (at high solids loading; ≥25% w/v). These included dilute acid and alkali hydrothermal, alkaline peroxide, caustic (NaOH) and microwave based autohydrolytical protocols which were all capable (under optimal conditions) of achieving close to 90% theoretical glucose yields when using an excess of cellulolytic enzyme. Optimisation of the enzymatic saccharification step was attempted and involved using a batch-fed protocol, with supplementary enzymes, and a high-torque mixing system were still only able to achieve ca. 43% theoretical glucose yields when operating at 15% w/v solids loading. Limited saccharification yields appear to be the rate limiting step for bioethanol production from BSG as it limited the concentration of glucose in the feedstocks produced. In addition, entirely biological routes to generate bioethanol were investigated using consolidated bioprocessing (CBP), which entailed using a consortium of fungal microorganisms. A primary filamentous fungal species was used as a cellulolytic enzyme factory whilst a yeast strain was used to ferment any liberated sugars to ethanol. From all of the fungal based CBP systems tested the traditional saké fermentation system (A.oryzae and S.cerevisiae NCYC479) was shown to achieve the highest ethanol yields (ca. 37 g/L within 10 days).